A case–control study of boat-related injuries and fatalities in Washington State. Issue 4 (31st March 2014) - Stempski, Sarah; Schiff, Melissa; Bennett, Elizabeth; Quan, Linda
Abstract : Objectives: To identify risk factors associated with boat-related injuries and deaths. Methods: We performed a case–control study using the Washington Boat Accident Investigation Report Database for 2003–2010. Cases were fatally injured boat occupants, and controls were non-fatally injured boat occupants involved in a boating incident. We evaluated the association between victim, boat and incident factors and risk of death using Poisson regression to estimate RRs and 95% CIs. Results: Of 968 injured boaters, 26% died. Fatalities were 2.6 times more likely to not be wearing a personal flotation device (PFD) and 2.2 times more likely to not have any safety features on their boat compared with those who survived. Boating fatalities were more likely to be in a non-motorised boat, to have alcohol involved in the incident, to be in an incident that involved capsizing, sinking, flooding or swamping, and to involve a person leaving the boat voluntarily, being ejected or falling than those who survived. Conclusions: Increasing PFD use, safety features on the boat and alcohol non-use are key strategies and non-motorised boaters are key target populations to prevent boating deaths.